RELEVANSI KEPENTINGAN ALAT-ALAT BUKTI DALAM PROSES PENYELESAIAN HUKUM PERDATA - Laily Az Zahra, Khansa; Mufid Al Amjad, Moh Fadwa; Nabya Maulidian, Syafa; Silvia, Septiani; Azfa Asyifa, Fadilla (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2024)
This paper discusses the important role of evidence in the civil law evidentiary process. Evidence allows parties to prove or disprove their claims in court. In this process, evidentiary tools such as written evidence, testimonies, depositions, admissions, and oaths become a solid foundation to build a legal case and help the court make a fair decision. The concept and classification of evidence, as well as their strength and hierarchy, become important factors in determining the success of a case in court. The method used is research that belongs to the type of analytical research. In the process, we analyze the relevance of evidence in the context of the case under study. In civil law settlements, the relevance of evidence is an essential aspect. Evidence plays a crucial role in ensuring justice and legal certainty. The classification of evidence, such as primary, secondary, and physical evidence, is important in assessing its probative force. Various theories of evidence, ranging from those that are bound by law to those that give judges freedom, offer diverse approaches in assessing evidence. Although they vary, the ultimate goal is to reach a fair verdict based on the available facts. By understanding and applying the concepts, strengths, hierarchies, and theories of evidence appropriately, the civil law settlement process can be carried out effectively, ensuring that the resulting decision is fair and in accordance with applicable legal principles.